Stressors of Rape Crisis Work From the Perspectives of Advocates With and Without Sexual Assault Victimization History - Mihelicova, Martina (Journal of interpersonal violence, 2021)
Rape crisis centers largely rely on volunteers for delivering emergency room advocacy to survivors of sexual assault. Volunteer advocates bear witness to trauma as part of their role, such as when listening to details of sexual assault. This exposure may negatively affect advocates long term, which may lead to secondary traumatic stress and vicarious traumatization, and possibly reduce their ability to provide quality services and remain in their role. In addition, some advocates may be survivors of sexual assault themselves. Survivors may differentially experience the toll of advocacy work. The present qualitative study sought to identify stressors that advocates face within their role, aspects of stressors unique to survivors who advocate, and the effects of stressors on advocates. Semistructured interviews were conducted with 18 current volunteer advocates, 11 of whom identified as survivors, from three rape crisis centers. Findings demonstrated stressors associated with self-evaluation; rules or expectations of the role (including the crisis nature of the role); witnessing lack of client support; helplessness around sexual assault as a systems issue; identifying with the client; witnessing the physical and emotional impact on clients; and being reminded of their own assault. Results also revealed how these stressors and advocacy overall influenced advocates. Unique aspects of stressors to survivors arose in the way advocates experienced the stressors. In addition, survivors exclusively described being reminded of past trauma within advocacy work. Findings have implications for supporting advocate well-being by better understanding the stressors that may lead to negative outcomes and informing individual coping, training, and overall organizational support of advocates. Such measures may ensure retention of volunteers and maintain quality advocacy services.